Preparation method of sulfide solid electrolyte membrane based on gradient polymer / ionic liquid composite binder and application and all-solid-state battery thereof

By designing a gradient polymer/ionic liquid composite binder, the problem of decreased ionic conductivity of sulfide electrolyte membranes under low pressure was solved, achieving high ionic conductivity and interface stability, thus promoting the industrialization of all-solid-state batteries.

CN120581677BActive Publication Date: 2025-11-11SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511086734.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-11-11
Estimated Expiration
2045-08-05

AI Technical Summary

Technical Problem

In commercial power batteries, sulfide electrolyte membranes suffer from reduced ionic conductivity due to module pressure limitations. Traditional binders are unable to effectively fill interparticle gaps under low pressure, failing to maintain long-term interface stability and affecting battery performance.

Method used

A gradient polymer/ionic liquid composite binder is used to form a continuous ionic conductive network through the plasticizing effect of the ionic liquid and the gradient coating process, providing mechanical support and ensuring high ionic conductivity under low pressure.

Benefits of technology

It significantly improves the ionic conductivity of sulfide electrolyte membranes under low pressure, reduces interparticle interface impedance, adapts to existing power battery production lines, and promotes the industrialization of sulfide solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120581677B_ABST
    Figure CN120581677B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder, its application, and an all-solid-state battery, belonging to the field of all-solid-state battery technology. The method employs a gradient coating process, first coating a polymer / ionic liquid / sulfide electrolyte composite layer, utilizing the plasticizing effect of the ionic liquid to fill the interparticle gaps under low pressure, reducing interfacial porosity; then coating a polymer / sulfide electrolyte surface layer to provide mechanical support and suppress electrode side reactions. This design enables the electrolyte membrane to maintain high ionic conductivity even under the operating pressure of commercial power battery modules, with reduced interfacial impedance compared to traditional homogeneous membranes. This invention, through innovative gradient structure and material combination, solves the ion transport bottleneck of sulfide electrolytes under low-pressure conditions, exhibiting excellent interfacial stability and process compatibility, providing a key technical solution for the industrialization of all-solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of all-solid-state battery technology, specifically relating to a method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder and its application, all-solid-state batteries, and especially a method for improving the ionic conductivity of a sulfide solid electrolyte membrane under low pressure by using a gradient polymer / ionic liquid composite binder. Background Technology

[0002] Sulfide solid electrolytes are considered ideal electrolyte materials for next-generation all-solid-state power batteries due to their high ionic conductivity at room temperature and good machinability. However, their commercial application faces key challenges: the ionic conductivity of sulfide electrolyte membranes is highly dependent on external pressure. Under high pressure (>30 MPa), close particle contact can be achieved, and the ionic conductivity is close to the theoretical value. However, in actual battery modules, due to limitations in packaging technology and mechanical design, the applied pressure is usually low (<1 MPa), leading to poor interparticle contact, increased porosity, and a significant decrease in ionic conductivity (by 1-2 orders of magnitude), severely affecting battery performance. In addition, volume changes in electrode materials during cycling further exacerbate interfacial contact failure, causing impedance increases and capacity decay.

[0003] Currently, traditional binders (such as PTFE and PVDF) have excessively high moduli, making it difficult to effectively fill interparticle gaps under low pressure, and they lack dynamic self-adaptation capabilities, thus failing to maintain long-term interfacial stability. Therefore, there is an urgent need to develop novel binder systems to optimize the interfacial contact of sulfide electrolyte particles under limited pressure conditions, while simultaneously ensuring mechanical support and electrochemical stability, in order to meet the demands of power batteries for high energy density, long cycle life, and low-cost manufacturing. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder, its application, and an all-solid-state battery, aiming to solve the problem of decreased ionic conductivity of sulfide electrolytes in commercial power battery applications due to module pressure limitations. The method significantly reduces the glass transition temperature of the polymer through the plasticizing effect of the ionic liquid, allowing the binder to remain flexible under low pressure and effectively fill the gaps between sulfide particles. Furthermore, through a gradient coating process, a polymer / ionic liquid / electrolyte composite layer is first coated, allowing the ionic liquid to form a continuous ionic conductive network at the particle interface, followed by a polymer / electrolyte surface layer to provide mechanical support. This design enables the electrolyte membrane to maintain high ionic conductivity under low pressure and effectively reduces interfacial impedance between particles.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] <First Aspect>

[0007] This invention provides a method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder, comprising the following steps:

[0008] Step 1: Mix the polymer and sulfide electrolyte powder and ball mill to obtain an electrolyte slurry containing polymer / sulfide;

[0009] Step 2: Mix and stir the ionic liquid with the lithium salt to obtain an ionic liquid-lithium salt solution;

[0010] Step 3: Mix the electrolyte slurry with the ionic liquid-lithium salt solution and ball mill to obtain a composite slurry;

[0011] Step 4: Coat the current collector with a composite slurry, let it dry, and then coat it with an electrolyte slurry to obtain the membrane material;

[0012] Step 5: Dry the membrane material and roll it to obtain the sulfide solid electrolyte membrane.

[0013] A further improvement of the present invention is that, in step 1, the polymer includes one or more of polyethylene oxide (PEO), polyisobutylene (PIB), cis-butadiene rubber (BR), and polyvinylidene fluoride (PVDF).

[0014] A further improvement of the present invention is that, in step 1, the sulfide electrolyte is a solid electrolyte of the Li6PS5Cl type.

[0015] A further improvement of the present invention is that, in step 1, the mass ratio of polymer to sulfide electrolyte is 2:98~10:90.

[0016] A further improvement of this invention is that, in step 1, the solvent used for mixing and ball milling is anhydrous acetonitrile. The ball milling speed during mixing and ball milling is 200~500 rpm; the ball milling time is 2~5 hours.

[0017] A further improvement of the present invention is that, in step 1, the solid content in the obtained electrolyte slurry containing polymer / sulfide is 25-40%.

[0018] A further improvement of the present invention is that, in step 2, the ionic liquid is a pyrrolidine-based ionic liquid; the ionic liquid includes one or more of N-methyl-N-propylpyrrolidine bisfluorosulfonylimide salt, N-methyl-N-ethylpyrrolidine bisfluorosulfonylimide salt, and N-methyl-N-butylpyrrolidine bistrifluoromethanesulfonylimide salt.

[0019] A further improvement of the present invention is that, in step 2, the lithium salt includes one or more of LiTFSI, LiPF6, LiBF4, LiDFOB, and LiFSI.

[0020] A further improvement of this invention is that, in step 2, the molar ratio of the ionic liquid to the lithium salt is 1:2 to 6, preferably 1:4. The ionic liquid and the lithium salt are mixed at a certain molar ratio, heated and stirred until a homogeneous transparent solution is formed, thereby obtaining an ionic liquid modified solution containing lithium salt.

[0021] A further improvement of this invention is that, in step 2, the mixing temperature is 50~80℃, the magnetic stirring speed is 600~1000 rpm, and the time is 4~8 hours. The lithium ion concentration in the ionic liquid-lithium salt solution is 0.8~1.5M.

[0022] A further improvement of the present invention is that, in step 3, the mass ratio of electrolyte slurry to ionic liquid-lithium salt solution is 15~20:1.

[0023] A further improvement of the present invention is that, in step 3, the rotation speed of the mixing ball mill is 200~500 rpm; the ball milling time is 2~5 hours, preferably 300 rpm, 4 hours.

[0024] A further improvement of this invention is that, in step 3, the solid content of the resulting composite slurry is 25-40%. Depending on the solid content requirement, a certain amount of anhydrous acetonitrile can be added before ball milling to adjust the viscosity.

[0025] A further improvement of the present invention is that, in step 4, the wet film thickness when coating the composite slurry is 80~150μm.

[0026] A further improvement of this invention is that, in step 4, the drying time is 20-40 minutes, preferably 30 minutes. Allowing the solvent to partially evaporate after about half an hour of natural drying allows the surface to be coated with an electrolyte slurry containing the polymer / sulfide.

[0027] A further improvement of the present invention is that, in step 4, the wet film thickness when coating the electrolyte slurry is 20~50μm.

[0028] A further improvement of the present invention is that, in step 4, the coating speed is 0.4~0.8 m / min.

[0029] A further improvement of this invention is that, in step 4, the current collector is a copper foil. The current collector is a negative electrode current collector.

[0030] A further improvement of this invention is that, in step 5, the drying temperature is 40~80℃, and the time is 8~15h. The drying process is vacuum drying, with a vacuum degree of 0.04~0.08 MPa.

[0031] A further improvement of this invention is that, in step 5, the rolling temperature is 60~100℃ and the pressure is 2~5MPa. After the rolling process, a dense gradient sulfide electrolyte membrane is obtained.

[0032] A further improvement of the present invention is that, in step 5, the thickness of the obtained sulfide solid electrolyte membrane is 80~130μm.

[0033] The present invention also provides an application of the sulfide solid electrolyte membrane obtained by the preparation method in the preparation of all-solid-state batteries.

[0034] The present invention also provides an all-solid-state battery comprising a sulfide solid electrolyte membrane obtained by the preparation method described above. The pressure during the preparation of the all-solid-state battery is 5~100MPa, preferably 60~100MPa.

[0035] During the fabrication of the all-solid-state battery, the stamping pressure is 50 kg to 1500 kg. This pressure refers to the external pressure that needs to be maintained on the mold after the battery is assembled in the mold.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) Under the working pressure of commercial power battery modules, the electrolyte membrane maintains a high ionic conductivity through the interfacial plasticizing effect of ionic liquid and gradient structure design, which is much higher than that of traditional homogeneous membranes.

[0038] (2) The unique gradient structure design enables the surface polymer / sulfide electrolyte layer to effectively block electrode side reactions, while the middle polymer / ionic liquid complex provides excellent interface self-adaptation capability and reduces interface impedance.

[0039] (3) By adopting quantifiable slurry preparation and gradient coating process, it can be fully adapted to existing power battery production lines and promote the industrialization of sulfide solid batteries. Attached Figure Description

[0040] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0041] Figure 1 This is a flowchart illustrating a method for preparing a sulfide solid electrolyte film based on a gradient polymer / ionic liquid composite binder, as provided in an embodiment of the present invention. Detailed Implementation

[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. The examples given are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0043] To facilitate understanding, the abbreviations or nouns mentioned in the text will be explained first:

[0044] N-Methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide ([Pyr 13 [TFSI]);

[0045] Polyethylene oxide (PEO);

[0046] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0047] Example 1

[0048] A method for preparing sulfide solid electrolyte films based on gradient polymer / ionic liquid composite binders, such as... Figure 1 As shown, the steps are as follows:

[0049] (1) Preparation of PEO / sulfide electrolyte slurry: The operation was carried out in an argon-filled glove box. 5.0g of polyethylene oxide (Mw=200,000) and 95.0g of Li6PS5Cl sulfide electrolyte powder (D50=3.2μm) were mixed, 200g of anhydrous acetonitrile solvent was added, and then the mixture was ball-milled at 300rpm for 4 hours to obtain a uniform PEO / electrolyte slurry with a solid content of 33.3%.

[0050] (2) Preparation of ionic liquid-lithium salt solution: N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt ([Pyr 13 [TFSI]) and LiTFSI were mixed at a molar ratio of 1:4, heated in an oil bath at 60°C and magnetically stirred (800 rpm) for 6 hours to obtain a transparent ionic liquid-lithium salt solution with a lithium ion concentration of 1.2M.

[0051] (3) Preparation of composite slurry: The operation is carried out in a glove box filled with argon. Take 100g of PEO / sulfide electrolyte slurry prepared in step 1, add 5.6g of ionic liquid-lithium salt solution from step 2, and then add 10g of anhydrous acetonitrile to adjust the viscosity. Ball mill at 300rpm for 4 hours to obtain a polymer / ionic liquid / electrolyte composite slurry with a final solid content of 35.2%.

[0052] (4) Gradient coating: The operation is carried out in a glove box filled with argon. First, a polymer / ionic liquid / electrolyte composite slurry is coated on a 12μm thick copper foil at a speed of 0.5m / min, and the wet film thickness is controlled at about 110μm. Let it air dry for 30 minutes. Then, a PEO / electrolyte slurry is coated on the surface at the same speed, and the wet film thickness is controlled at about 40μm.

[0053] (5) Drying and hot pressing: The coated membrane material is transferred to a vacuum drying oven for drying at a temperature of 50℃ and a vacuum degree of 0.05 MPa for 12 hours. Then the dried membrane material is placed in a hot press for rolling treatment at a temperature of 80℃ and a pressure of 2.5 MPa for 3 times to finally obtain a dense gradient sulfide electrolyte membrane with a thickness of about 110 μm.

[0054] Example 2

[0055] A method for preparing sulfide solid electrolyte films based on a gradient polymer / ionic liquid composite binder, comprising the following steps:

[0056] (1) Preparation of PEO / sulfide electrolyte slurry: In an argon-filled glove box, 8.0g of polyethylene oxide and 92.0g of Li6PS5Cl sulfide electrolyte powder were mixed, 250g of anhydrous acetonitrile solvent was added, and the mixture was ball-milled at 400rpm for 3 hours to obtain a uniform PEO / electrolyte slurry with a solid content of 28.6%.

[0057] (2) Preparation of ionic liquid-lithium salt solution: N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide and LiTFSI were mixed at a molar ratio of 1:5 and magnetically stirred (900 rpm) in an oil bath at 70°C for 6 hours to obtain a transparent ionic liquid-lithium salt solution with a lithium ion concentration of 1.0 M.

[0058] (3) Preparation of composite slurry: In an argon glove box, take 150g of the slurry from step 1, add 9.0g of the ionic liquid-lithium salt solution from step 2, add 15g of anhydrous acetonitrile to adjust the viscosity, and ball mill at 300rpm for 4 hours. The final solid content of the slurry is 30.2%.

[0059] (4) Gradient coating: Coat the composite slurry on a 12μm thick copper foil at a speed of 0.6m / min, with the wet film thickness controlled at about 120μm, and let it air dry for 30 minutes; then coat the surface layer with PEO / electrolyte slurry at the same speed, with the wet film thickness controlled at about 30μm.

[0060] (5) Drying and hot pressing: The coated membrane material is transferred to a vacuum drying oven for drying at a temperature of 60℃ and a vacuum degree of 0.06 MPa for 10 hours. Then, the dried membrane material is placed in a hot press for rolling treatment at a temperature of 85℃ and a pressure of 3.0 MPa. The rolling is repeated 3 times to finally obtain a dense gradient sulfide electrolyte membrane with a thickness of about 110 μm.

[0061] Comparative Example 1

[0062] A method for preparing a sulfide solid electrolyte film, the steps of which are basically the same as those in Example 1.

[0063] Steps (2) and (3) in Example 1 are omitted, and PEO / sulfide electrolyte slurry is directly used for one-time coating. The wet film thickness is controlled at about 150 μm, and the other parameters remain unchanged.

[0064] Comparative Example 2

[0065] A method for preparing a sulfide solid electrolyte film, the steps of which are basically the same as those in Example 1.

[0066] In step (4), a polymer / ionic liquid / electrolyte composite slurry is used for one-time coating, and the wet film thickness is controlled at about 150 μm, while the other parameters remain unchanged.

[0067] Comparative Example 3

[0068] A method for preparing a sulfide solid electrolyte film, the steps of which are basically the same as those in Example 1.

[0069] In step (2), N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide (pyrrolidine ionic liquid) was replaced with 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (imidazolium ionic liquid). Imidazole ionic liquids have lower compatibility with sulfide electrolytes than pyrrolidine ionic liquids. Then, a film was formed by gradient coating, with the other parameters remaining unchanged.

[0070] Comparative Example 4

[0071] A method for preparing a sulfide solid electrolyte film, the steps of which are basically the same as those in Example 1.

[0072] The polymer / ionic liquid / electrolyte composite slurry and PEO / electrolyte slurry used in coating are directly mixed, and the mixed slurry is used for coating, with the wet film thickness controlled at about 150μm.

[0073] Detection and analysis:

[0074] The examples and comparative examples were tested using the following methods:

[0075] The electrolyte membranes prepared in each embodiment and comparative example were cut into small circular pieces with a diameter of 10 mm, loaded into a pressure battery mold, and pressed for 1 minute under a pressure of 1 ton, and then held for 1 minute. An electrochemical workstation of model CHI660E was used to conduct AC impedance testing at room temperature. During the test, the pressure of the pressure mold was maintained at 1 ton, which is 127 MPa. The test results are shown in Table 1.

[0076] Table 1: Electrochemical performance data of sulfide electrolyte membranes at 127 MPa

[0077]

[0078] The same sample preparation and testing method was used, except that the pressure of the pressure mold was maintained at 0.5 tons during the test, with a pressure of 63.5 MPa. The test results are shown in Table 2.

[0079] Table 2: Electrochemical performance data of sulfide electrolyte membranes at 63.5 MPa

[0080]

[0081] The same sample preparation and testing method was used, except that the pressure of the pressure mold was maintained at 100 kg during the test, and the pressure was 12.7 MPa. The test results are shown in Table 3.

[0082] Table 3: Electrochemical performance data of sulfide electrolyte membranes at 12.7 MPa

[0083]

[0084] As can be seen from Table 1, under a high pressure of 127 MPa, the impedance and ionic conductivity of the examples and comparative examples are not significantly different. However, the impedance of the electrolyte membranes of Examples 1 and 2 is still lower than that of Comparative Examples 1-3, while the ionic conductivity of Examples 1 and 2 is higher than that of Comparative Examples 1-3.

[0085] As can be seen from Table 2, under a medium pressure of 63.5 MPa, the impedance of Comparative Examples 1-3 showed a significant increase, and the ionic conductivity of the comparative examples was lower than that of the examples.

[0086] As can be seen from Table 3, under a low pressure of 12.7 MPa, the impedance of the comparative sample increases sharply, and its ionic conductivity is an order of magnitude lower than that of the example.

[0087] As can be clearly seen from the above, the method provided by the present invention has a significant effect on improving the ionic conductivity of sulfide electrolyte membranes under low pressure.

[0088] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that these are merely illustrative examples, and any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder, characterized in that, Includes the following steps: Step 1: Mix the polymer and sulfide electrolyte powder and ball mill to obtain an electrolyte slurry containing polymer / sulfide; Step 2: Mix and stir the ionic liquid with the lithium salt to obtain an ionic liquid-lithium salt solution; Step 3: Mix the electrolyte slurry with the ionic liquid-lithium salt solution and ball mill to obtain a composite slurry; Step 4: Coat the composite slurry onto the current collector, let it dry, and then coat it with the electrolyte slurry to obtain the membrane material; Step 5: Dry the membrane material and roll it to obtain the sulfide solid electrolyte membrane. In step 2, the ionic liquid includes one or more of N-methyl-N-propylpyrrolidine bisfluorosulfonylimide salt, N-methyl-N-ethylpyrrolidine bisfluorosulfonylimide salt, and N-methyl-N-butylpyrrolidine bistrifluoromethanesulfonylimide salt.

2. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 1, the polymer includes one or more of polyethylene oxide, polyisobutylene, cis-butadiene rubber, and polyvinylidene fluoride; And / or, in step 1, the sulfide electrolyte is a solid electrolyte of the Li6PS5Cl type; And / or, in step 1, the mass ratio of polymer to sulfide electrolyte is 2:98~10:90; And / or, in step 1, the solid content in the resulting electrolyte slurry containing polymer / sulfide is 25-40%.

3. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 2, the lithium salt includes one or more of LiTFSI, LiPF6, LiBF4, LiDFOB, and LiFSI.

4. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 2, the molar ratio of ionic liquid to lithium salt is 1:2~6; And / or, in step 2, the mixing speed is 600~1000 rpm, and the time is 4~8h; And / or, in step 2, the mixing temperature is 50~80℃.

5. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 3, the mass ratio of electrolyte slurry to ionic liquid-lithium salt solution is 15~20:

1.

6. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 3, the solid content of the resulting composite slurry is 25-40%.

7. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 4, the wet film thickness when coating the composite slurry is 80~150μm; And / or, in step 4, the wet film thickness when coating the electrolyte slurry is 20~50μm; And / or, in step 4, the coating speed of the composite slurry and the electrolyte slurry is 0.4~0.8m / min.

8. The method for preparing a sulfide solid electrolyte membrane based on a gradient polymer / ionic liquid composite binder according to claim 1, characterized in that, In step 5, the drying temperature is 40~80℃ and the time is 8~15h; And / or, in step 5, the drying process is vacuum drying, with a vacuum degree of 0.04~0.08 MPa; And / or, in step 5, the temperature of the rolling process is 60~100℃; the pressure is 2~5MPa; And / or, in step 5, the thickness of the sulfide solid electrolyte membrane is 80~130μm.

9. The application of a sulfide solid electrolyte membrane obtained by the preparation method as described in claim 1 in the preparation of all-solid-state batteries.

10. An all-solid-state battery comprising a sulfide solid electrolyte membrane obtained by the preparation method as described in claim 1.

Citation Information

Patent Citations

  • Solid electrolyte membrane with gradient structure as well as preparation method and application of solid electrolyte membrane

    CN117673441A

  • Multilayer electrolyte cell, secondary battery comprising multilayer electrolyte cell and manufacturing method therefor

    US20180358652A1